2022
DOI: 10.1021/acsnano.2c00513
|View full text |Cite
|
Sign up to set email alerts
|

Universal p-Type Doping via Lewis Acid for 2D Transition-Metal Dichalcogenides

Abstract: Developing spatially controlled and universal p-type doping of transition-metal dichalcogenides (TMDs) is critical for optoelectronics. Here, a facile and universal p-doping strategy via Sn4+ ions exchanging is proposed and the p-doping of PdSe2 is demonstrated systematically as the example. The polarity of PdSe2 can be modulated from n-type to bipolar and p-type precisely by changing the concentration of SnCl4 solution. The modulation effectively reduces the electron concentration and improves the work functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
(42 reference statements)
1
25
0
Order By: Relevance
“…The photoresponse time can also be obtained in the inset. The rising and falling times, defined as the time interval between 10 and 90% of the peak of the photocurrent, are determined to be 120 and 210 μs, respectively, which is faster than those of previously reported works. The wavelength-dependent photoresponse of the MoTe 2 /MoSe 2 p–n photodetector was also studied. As shown in Figure S16a,b, obvious photoresponse can be observed at zero bias for a broad range of wavelengths, from ultraviolet (365 nm) to NIR (1045 nm), demonstrating the broadband detection capability of our self-driven photodetector.…”
Section: Resultsmentioning
confidence: 86%
“…The photoresponse time can also be obtained in the inset. The rising and falling times, defined as the time interval between 10 and 90% of the peak of the photocurrent, are determined to be 120 and 210 μs, respectively, which is faster than those of previously reported works. The wavelength-dependent photoresponse of the MoTe 2 /MoSe 2 p–n photodetector was also studied. As shown in Figure S16a,b, obvious photoresponse can be observed at zero bias for a broad range of wavelengths, from ultraviolet (365 nm) to NIR (1045 nm), demonstrating the broadband detection capability of our self-driven photodetector.…”
Section: Resultsmentioning
confidence: 86%
“…A carrier concentration comparison of BiCuSeO and other typical p‐type 2D semiconductors is shown in Table 1 . [ 44–54 ] The mobility of BiCuSeO is ≈196 cm 2 V −1 s −1 at 2 K. It is noteworthy that the carrier concentration and mobility of 2D BiCuSeO nanosheets sharply change when the temperature is over ≈130 K. A maxima value arising at ≈126 K in the bottom‐right inset in Figure 3c indicates that these phenomena can be assigned to a phase transition of 2D BiCuSeO nanosheets. Although similar behaviors were reported in bulk BiCuSeO, [ 16,17 ] the origin of this phase transition is still ambiguous.…”
Section: Resultsmentioning
confidence: 93%
“…The resultant uniform doping reduces the process's controllability and selectivity. Therefore, researchers have come up with various post-growth substitutional methods such as plasma etching, [181][182][183] solution-phase ion exchanging, [184] post-synthesis annealing, [185,186] and photoinduced doping. [187,188] For instance, the formerly mentioned nitrogen doping can also be established through N 2 plasma treatment.…”
Section: Substitutional Doping and Alloyingmentioning
confidence: 99%
“…[183] Similar maskassisted patterned doping is also demonstrated in solution-phase ion exchanging. [184] Li et al [184] reported a highly spatially confined p-type doping method in TMDs through Sn 4+ ions exchanging. PdSe 2 was taken as an example in their work to demonstrate the feasibility.…”
Section: Substitutional Doping and Alloyingmentioning
confidence: 99%